The haunted opera : a Marie-Grace mystery - Buckey, Sarah Masters, 1955- (American Girl mysteries., 2013)
Marie-Grace is excited that a well-known English opera company will perform at the very theater where she takes singing lessons from Aunt Océane, but as she and her friend Cécile help out backstage, the make disturbing discoveries.